Mapping mathematical competences across subjects for advanced level qualifications in England - Norris, Jennifer; Noyes, Andrew (The Curriculum Journal, 2023)
Efforts to increase the number of young people in England studying mathematics post-16 have historically focused on participation in standalone mathematics qualifications. However, following the recent A-level reforms, many advanced level students are engaging with some form of mathematics through the mathematical content now formally embedded within other subjects. To offer a more comprehensive view of the mathematics being learned post-16 we present a framework analysis of the subject content documents of the 19 A-level subjects with a required quantitative component, using a recently developed framework of General Mathematical Competences (GMCs). Results are visualised as maps showing the presence of GMC sub-competences for individual A-level subjects and combinations of subjects. The application of the GMC framework in this new context provides a much-needed common language for cross-curricular discussion of the types of mathematics present in different subjects, with implications for interdisciplinary mathematics learning and curriculum alignment between post-16 and higher education across the disciplines. In addition, the framework highlights the non-binary nature of mathematics participation, calling into question what counts as participating in mathematics in the post-16 phase.
_eprint: https://onlinelibrary.wiley.com/doi/pdf/10.1002/curj.204
Keywords: interdisciplinary mathematics; mathematical competences; participation; post-16